2009
DOI: 10.3945/ajcn.2009.28371
|View full text |Cite
|
Sign up to set email alerts
|

Eating out of home in Vietnamese adolescents: socioeconomic factors and dietary associations

Abstract: OH eating added a number of desirable foods and nutrients but was also associated with higher consumption of energy from fat and sugar products. Independent of household wealth and locality, pocket money and sex are important determinants of OH eating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
67
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 45 publications
10
67
0
4
Order By: Relevance
“…The finding brings to our attention that children receiving pocket money visit fast food stalls frequently and unhealthy diet and lifestyles can be risk factors for future lifestyle diseases. Carl Lachat et al, in their study on Vietnamese adolescents concluded that the amount of pocket money received was positively associated with consumption of eating out of home foods [18]. Mishra and Singh also showed in their study on teenagers that those who have pocket money (Rs.…”
Section: Resultsmentioning
confidence: 94%
“…The finding brings to our attention that children receiving pocket money visit fast food stalls frequently and unhealthy diet and lifestyles can be risk factors for future lifestyle diseases. Carl Lachat et al, in their study on Vietnamese adolescents concluded that the amount of pocket money received was positively associated with consumption of eating out of home foods [18]. Mishra and Singh also showed in their study on teenagers that those who have pocket money (Rs.…”
Section: Resultsmentioning
confidence: 94%
“…In Vietnam, out-of-home traditional street foods contributed a higher percentage to daily sodium intake among urban adolescents compared with rural adolescents (33.1 ± 2.1 % vs. 12.1 ± 2.1 %, respectively). However, rural adolescents had higher total sodium intakes compared with urban adolescents (1643.2 ± 124.8 mg Na vs. 1500.7 ± 124.8 mg Na, respectively) [ 32 ]. In Singapore, data from the Singapore Chinese Health Study showed that respondents reporting frequent intake of Western-style fast food items (≥2 times/week) also consumed more dim sum , noodles, and sugar-sweetened beverages, and greater amounts of sodium (864 mg Na/1000 kcal) compared with those who did not eat fast foods (651.7 mg Na/1000 kcal) [ 33 ].…”
Section: Impact Of Urbanization On the Amount Of Sodium In The Southementioning
confidence: 99%
“…5,10,13,20 Soft drinks, alcoholic drinks and savory snacks were those food groups most frequently consumed outside of the home in other studies. 14,18,19,24 Fried and roasted snacks characteristic to Brazil are cheaper than meals and fast food. 3 The percentage of high calorie, low nutrient food consumed outside of the home was greater among adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also identifi ed higher frequency of eating out among the young and among men, 8,12,13,23 as well as the association between demand for eating out and income or indicators of income such as schooling and employment situation. 2,14,23 In Brazil, a 10% increase in income contributed to a 3% rise in food bought to be consumed outside of the home. 7 In contrast to what has been observed in the United States, 2,23 the presence of children and family size were not associated with frequency of eating out in Brazil, except in the North and Northeast regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation